Level of Knowledge Management Orientation, Marketing Capability and Firm Performance among the trained and untrained agri-input retailers - M. Malarkodi; N. Deepa; S.D. Sivakumar; K. Divya (Journal of Agricultural Extension Management, 2016)
The increasing importance of knowledge in the modern and globalized Organization has initiated a need to focus on managing knowledge as an Organizational and competitive asset. The traditional agri-input retailers located in villages had played a significant role in the agricultural production process. Several studies have indicated that they had been the primary source of information to the farmers on cultivation aspects. Their presence in the village at all times. familiarity of being known as a village person, provision of credit sales etc., had made them indispensable to farmers. Considering the above aspects, a study was undertaken to analyse the level of Knowledge Management Orientation (KMO), Marketing Capability (MC) and Firm Performance (FMP) among the trained and untrained agri-input retailers in the western zone of Tamil Nadu. The total sample size was 240 agriinput retailers (120 trained and 120 untrained retailers) drawn from the population of study. A well structured interview schedule was prepared and mean score analysis was used to analyse the level of KMO, MC and FMP. The Willcoxon Matched pairs Test was used to determine the significance of the difference in mean values of KMO, MC and FMP between trained and untrained agri-input retailers. It was found that there was a significant difference in KMO, MC and FMP between the trained and untrained agriinput retailers. The authors conclude that steps must be taken by training institutions to impart training focused on providing information on both technological and marketing capability related aspects